PERANCANGAN TUNER GITAR OTOMATIS DENGAN METODE OPEN TUNING BERBASIS SINGLE BOARD MICROCONTROLLER - Adlan Bagus Pradana; Achmad Dian Ramadhan; Jimmy Trio Putra; Aldila Fajar (Universitas Sarjanawiyata Tamansiswa, 2021)
The guitar is a popular musical instrument by many people. Besides being able to be used as entertainment, playing music, one of which is the guitar, can also be used to train concentration. In playing the guitar, the sound of the guitar strings that match the harmony chord is the main key so that when playing the song it sounds harmonious. Of course this is related to the tuning process or the tuning process. Many people can play the guitar, but many of them have difficulty in tuning. Most people do the tuning manually. This of course will take a long time to produce an accurate tone.With the rapid development of technology, this problem can be solved with an automatic guitar tuner based on a single board microcontroller using the open tuning method. The design of this automatic guitar tuner uses 7 constituent components, namely a single board microcontroller (Arduino UNO), servo motor, Op-Amp, LED, LCD, push button, and acrylic. The tuning process is done by selecting the guitar strings to be tuned. Then, when the guitar is picked, the frequency will be amplified by the Op-Amp. After that, arduino will initialize the frequency and give a signal to the servo motor. The servo motor will perform the tuning process which will later display the results on the LCD. While the LED functions as a tuning indicator. Acrylic serves as a place to put components.